2013
DOI: 10.1109/tpwrs.2012.2209902
|View full text |Cite
|
Sign up to set email alerts
|

Application of plug-in electric vehicles to frequency regulation based on distributed signal acquisition via limited communication

Abstract: For application of a large number of plug-in electric vehicles (PEVs) to system frequency regulation, a distributed acquisition approach based on consensus filtering is proposed, where frequency-measuring function is performed only at distribution substations. Limited communication between neighboring PEVs/distribution substations can facilitate consistent and accurate acquisition of frequency deviation signals for all PEVs. Considering the battery charging/discharging characteristics, a dynamic PEV model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 26 publications
0
65
0
1
Order By: Relevance
“…Flattening power load is further demonstrated to be effective to improve energy efficiency and power loss of the power grid [6]. The second thread is frequency regulation and example studies include [31,32,33,34,35]. A gap between power supply and demand on the power grid causes the grid frequency to deviate from its nominal value, and the goal of frequency regulation is to reduce this gap.…”
Section: Electric Vehicle Charging Overviewmentioning
confidence: 99%
“…Flattening power load is further demonstrated to be effective to improve energy efficiency and power loss of the power grid [6]. The second thread is frequency regulation and example studies include [31,32,33,34,35]. A gap between power supply and demand on the power grid causes the grid frequency to deviate from its nominal value, and the goal of frequency regulation is to reduce this gap.…”
Section: Electric Vehicle Charging Overviewmentioning
confidence: 99%
“…In addition, controlling the input power of PEV batteries has been widely studied to provide ancillary services to AC or DC microgrids and distribution networks. For example, the response of PEVs to frequency control signals was investigated in [16][17][18][19][20][21][22][23][24][25]. Specifically, a proportional controller and a high-pass filter were used to adjust the PEV input power in [16,17], respectively, to reduce the battery power capacity required for a stabilized frequency control.…”
Section: Devicementioning
confidence: 99%
“…For example, optimal dispatch and control approaches for EVs are discussed in [8][9][10][11]; the vehicle-to-grid (V2G) potentials of EVs in energy trading and ancillary services are studied in [12][13][14][15][16]; the coordination of EVs and the volatile renewable energy sources are examined in [17][18][19][20]; the impacts of flexible EVs on generation expansion planning [21,22]; the EV (2) It has been confirmed that battery discharging has a negative impact on the battery life [34,35], and this means that the EV customer will suffer from extra economic loss than in the ordinary charging mode without V2G, if no compensation is provided. The degradation process of EV batteries are modeled in detail and analyzed based on factors such as the driving patterns of EVs, impacts of the depth-of-discharge and ambient temperatures in [35,36].…”
Section: Introductionmentioning
confidence: 99%